Inhibition of Apoptosis of Liver Cells of Mice Infected With Plasmodium berghei Through The Expression of Caspase-3 Using Sargassum duplicatum Extract - Abdul M Ukratalo (Nusantara Scientific Medical, 2022)
The process of apoptosis is an integrated process between external and internal factors involving several enzymes (Caspase-9, -8, -7, -6, -3) that act as major players in the process of apoptosis. This research aims to determine the potential of brown algae methanol extract Sargassum duplicatum against inhibition of apoptosis of liver cells of mice infected with Plasmodium berghei through the expression of caspase-3. Mice weighing 20–30 grams in Plasmodium berghei infection as much as 0.1 ml per head and left until the percent of parasitemia reaches 1-5%. Then mice (Mus musculus) were given methanol extract of Sargassum duplicatum seaweed at a dose of 1 gr / 100 ml, 10 gr / 100 ml, 100, gr / 100 ml, and 200 gr / 100 ml for 4 consecutive days and observed until day 6. After that, a histological preparation was made with immunohistochemistry staining to see the expression of caspase-3. The results of the observations will be analyzed descriptively. The results showed that Sargassum duplicatum methanol extract was able to inhibit liver cell apoptosis in mice infected with Plasmodium berghei. The decrease in Caspase-3 expression in this study is thought to be caused because the brown algae Sargassum duplicatum contains flavonoid compounds, tannins, and saponins which can reduce the pro-inflammatory cytokine caspase-3 through the role of NF-kB which is a transcription factor that plays a role in stimulating and coordinating innate and adaptive immune responses.